Sex differences of in-hospital outcome and long-term mortality in patients with Takotsubo cardiomyopathy - Weidner, Kathrin; El-Battrawy, Ibrahim; Behnes, Michael; Schramm, Katja; Fastner, Christian; Kuschyk, Jürgen; Hoffmann, Ursula; Ansari, Uzair; Borggrefe, Martin; Akın, Ibrahim (Therapeutics and clinical risk management, 2017)
Sex differences of in-hospital outcome and long-term mortality in patients with Takotsubo cardiomyopathy KJ Weidner,1,* I El-Battrawy,1,2,* M Behnes,1 K Schramm,1 C Fastner,1,2 J Kuschyk,1 U Hoffmann,1,2 U Ansari,1 M Borggrefe,1,2 I Akin1,2 1First Department of Medicine, University Medical Centre Mannheim, Faculty of Medicine Mannheim, University of Heidelberg, 2DZHK (German Center for Cardiovascular Research), Partner Site, Heidelberg, Mannheim, Germany *These authors contributed equally to this work Background: Previous studies revealed that patients with Takotsubo cardiomyopathy (TTC) have a higher mortality rate than the general population. It is still unclear whether sex differences may influence long-term prognosis of TTC patients. The purpose of this study was to determine whether sex differences do influence the short- and long-term outcomes of TTC. Methods and results: A total of 114 patients with TTC were admitted to the University Medical Centre Mannheim from January 2003 to September 2015 and entered into the TTC database of the University Medical Centre Mannheim, and retrospectively analyzed. Patients were diagnosed by the Mayo Clinic criteria. All-cause mortality over mean follow-up of 1,529±1,121 days was revealed. Significantly more male patients died within long-term follow-up compared to female TTC patients (log-rank test; P=0.01). Most males died of noncardiac causes. In multivariate Cox regression analysis, the male sex (P=0.02, hazard ratio [HR] 2.8, 95% CI 1.1–7.2), the ejection fraction ≤35% (P=0.01, HR 3.3, 95% CI 1.2–9.2) and glomerular filtration rate <60 mL/min (P<0.01, HR 3.1, 95% CI 1.4–7.0) figured out as independent predictors of the adverse outcome. Conclusion: This study shows that males suffering from TTC reveal a higher long-term all-cause mortality rate than females over a 5 year follow-up period. Keywords: Takotsubo cardiomyopathy, sex differences, outcome, mortality